Hakikaт Kepemimpinan Perempuan: Sebuah Refleksi Sejarah : The Reality Of Women's Leadership: A Historical Reflection - Fathunnurohmiyati (An-Nisa’ Journal of Gender Studies, 2015)
The Qur'an and Islamic history mention many strong women who can be used as role models or examples to understand the essence of female leadership in life. Not only are virtuous women immortalized in the Qur'an as a source of inspiration for women's lives, but in some of its verses, the Qur'an also immortalizes women who met with misfortune, so that their actions may serve as a lesson for future generations. There are types of warriors with unwavering faith, there are righteous women who are steadfast in worship and consistently maintain their purity, and there are also types of instigators, seducers, and traitors. It depends on how the reader reflects on and applies these lessons in daily life. Dalam Al-Qur'an dan Sejarah Islam sudah banyak menyebutkan perempuan-perempuan tangguh yang bisa dijadikan sebagai suritauladan atau contoh untuk memahami esensi kepemimpinan perempuan dalam kehidupan. Tidak hanya perempuan sholehah yang di abadikan dalam AlQur'an untuk menjadi sumber inspirasi bagi kehidupan kaum perempuan, dalam beberapa ayatnya, Al-Qur'an juga mengabadikan kaum perempuan yang celaka, agar apa yang mereka lakukan dapat dijadikan pelajaran bagi kaum sesudahnya. Ada tipe pejuang yang kokoh keimanannya, ada wanita shalihah yang tangguh dalam ibadah dan konsisten menjaga kesucian diri, ada pula tipe penghasut, penggoda, dan pengkhianat. Tergantung bagaimana pembaca merfleksikan untuk diaplikasikan dalam kehidupan sehari-hari